Country performance at the International Mathematical Olympiad - Golo Henseke (Universität Rostock, Institut für Volkswirtschaftslehre, 2009)
This study seeks to explain country differences in the performance at the International Mathematical Olympiad. Hypotheses on the relationship between, on one hand, performance at the Olympiads and, on the other, population size and dynamics, economic resources, human capital, schooling quantity and quality, and the political regime are tested with a panel dataset of 97 countries over the period 1993-2006. The analysis distinguishes between crosscountry differences and intra-country differences. Results indicate that macro-conditions explain cross-country differences well but fail to predict changes in performance over time. Thus, long-term differences in country characteristics are associated with the average performance of Olympians.
Keywords: I21; H52; J24; 330; Science Olympiads; Talent in mathematics; Country panel; PISA; Hochqualifizierte Arbeitskräfte; Mathematik; Bildungsniveau; Standortfaktor; Makroökonomischer Einfluss